Desenvolvimento de uma ferramenta baseada na linguagem Query by Example para criação e execução de consultas SQL - Nogueira, Ana Lívia (2018)
This monograph presents the concepts and a prototype of a tool to simplify the preparation of SQL queries for the PostgreSQL database, as well as the execution of the queries, using the Query by Example (QBE) technique. The technique allows the user / programmer to create complex queries through a simple and intuitive visual interface. The tool can also be used to teach the SQL language because from the visual query a query in the SQL language is presented. The tool was developed in Visual Basic.net as a desktop application on the Microsoft Windows platform. To make the connection between the VB.net application and the PosgreSQL database, the NpgSQL data provider was used. The tool is able to perform the connection to the database, retrieve the available tables and their attributes so that the user can visually elaborate simple queries that can involve more than one table. Finally, the tool displays the query in SQL and the results in tabular form. This study will serve as a basis for future work and more functionality can be added to the tool, including aggregation functions.